2016
DOI: 10.1038/mt.2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Virus-mediated EpoR76E Therapy Slows Optic Nerve Axonopathy in Experimental Glaucoma

Abstract: Glaucoma, a common cause of blindness, is currently treated by intraocular pressure (IOP)-lowering interventions. However, this approach is insufficient to completely prevent vision loss. Here, we evaluate an IOP-independent gene therapy strategy using a modified erythropoietin, EPO-R76E, which has reduced erythropoietic function. We used two models of glaucoma, the murine microbead occlusion model and the DBA/2J mouse. Systemic recombinant adeno-associated virus-mediated gene delivery of EpoR76E (rAAV.EpoR76E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 41 publications
9
44
0
Order By: Relevance
“…Consistent with previously published studies (Sappington et al, 2010; Lambert et al, 2011; Ward et al, 2014; Bond et al, 2016), microbead-induced IOP elevation in WT mice resulted in a 50% decrease in anterograde transport of CTB to the SC (Figure 3). Interestingly, IL-6 -/- mice exhibited a similar decrease in anterograde transport (Figure 3).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previously published studies (Sappington et al, 2010; Lambert et al, 2011; Ward et al, 2014; Bond et al, 2016), microbead-induced IOP elevation in WT mice resulted in a 50% decrease in anterograde transport of CTB to the SC (Figure 3). Interestingly, IL-6 -/- mice exhibited a similar decrease in anterograde transport (Figure 3).…”
Section: Discussionsupporting
confidence: 91%
“…To allow local expression of targeted inhibitors of C3 activation to the retina of DBA/2J mice, we adopted ocular gene therapy using high-efficiency triple Y-F mutant capsid AAV2 vectors, which result in widespread and stable transduction of RGCs and inner retina in adult mice 47 . We performed bilateral, intravitreal injections of AAV2.GFP reporter at 10 10 total vector genomes per eye in 7 month-old DBA/2J mice, and confirmed efficient transduction of the inner retina in 10 month-old mice, consistent with previous reports of DBA/2J viral gene therapy [48][49][50][51] . Retinal wholemounts and radial sections showed GFP expression in the nerve fiber layer (NFL) and ganglion cell layer (GCL) (Figure 1A, B).…”
Section: Intravitreal Aav2cr2-crry Limits the Deposition Of C3d On Rgcssupporting
confidence: 87%
“…Ocular gene therapy viral vectors, such as adeno-associated virus (AAV), have been used to provide the diseased retina with local and permanent expression of Crry and other inhibitors, to chronically attenuate complement activation in models of age related macular degeneration [44][45][46] . Serotype 2 AAV vectors yield widespread transduction of the inner retina and RGCs 1 month after intravitreal injection in the mouse eye 47 , and over 10 months in the DBA/2J retina [48][49][50][51] . Thus, stable expression of targeted complement inhibitors via AAV gene therapy should be a viable approach to chronically attenuate complement activation during DBA/2J glaucoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by Sullivan et al, demonstrated that AAV-mediated delivery of erythropoietin (AAV.EPOR76E) protected RGCs and axons in the D2 model of glaucoma (83). However, an additional study was performed to determine if the AAV.EPOR76E could also protect RGC axons in the mouse microbead occlusion model of elevated IOP and while the AAV.EPOR76E treated group appeared to have fewer degenerating axons when compared to the untreated group, there was no significant difference in the total number of axons between groups (84). …”
Section: Discussionmentioning
confidence: 99%